Synchronizing the Baltic States’ Grid with Europe as a Strategic Move for Regional Security - Muhammad, Andi Fachri (Department of International Relations, Brawijaya University, 2025)
The Baltic states of Estonia, Latvia and Estonia are currently facing a predicament in the energy sector. After years of occupation under the Soviets, the Baltic states are trying to distance themselves politically as far away from Russian influence. However, the three Baltic states were still importing electricity from the large, yet also perceived hostile, electricity provider. Geopolitical changes especially after the Russian military advanced into Ukraine caused concern within the Baltic states, including fears of electricity sabotage. As such, they decided to act to protect their national infrastructure and interests by cooperating with the EU to develop a stronger and more inter-connected power grid. One way to do this is to disconnect the Baltic states’ grids away from Russia and into the European network. Through the primary and secondary data gathered, the explanative method shall be used on using the theories of Liberalism and Securitization. These two theories will be used to define the history, the capability, and the impact each three Baltic state and the EU have throughout the synchronization process, which would end up materializing on the 9th of February 2025.